Exploring barriers to the adoption and utilization of improved latrine facilities in rural Ethiopia: An Integrated Behavioral Model for Water, Sanitation and Hygiene (IBM-WASH) approach. - Aiggan Tamene; Abel Afework (PLoS ONE)
Background Even though evidence shows that access to and use of improved latrines is related to healthful families and the public, obstacles to the adoption and use of improved latrine facilities remain. Globally, not many inquiries appear to have been carried out to satisfactorily inform us regarding the multi-level barriers influencing the adoption and utilization of improved latrines facilities. Related studies in Ethiopia are even fewer. Methods Two qualitative data gathering methods, viz., key informant interviews and focus group discussions, were employed to collect data for this study. A total of fifteen focus group discussions were conducted with members of the community in the rural Wonago district of Ethiopia. Similarly, ten key informant interviews were conducted with water, sanitation, and hygiene officers, and health extension workers responsible for coordinating sanitation and hygiene activities. Open code software 4.03 was used for thematic analysis. Result Barriers to adoption and use of improved latrine facilities were categorized into Contextual factors (e.g. Gender, educational status, personal preference for using the field, limited space, population density, the status of land ownership), Psychosocial factors (Culture, beliefs, attitudes, and perceptions of minimal health threat from children's feces), and Technological factors (inconveniences in acquiring materials and cost of constructing a latrine). Conclusion There are a series of multi-leveled barriers to the sustained adoption and use of latrines. Providing funding opportunities for the underprivileged and offering training on the engineering skills of latrine construction at the community level based on the contextual soil circumstances could expand the latrine coverage and use. Similarly, taking into account the variability in motivations for adopting and using latrines among our study in Ethiopia and other studies, we implore public health experts to recognize behaviors and norms in their target communities in advance of implementing sanitation interventions.